THE CONCEPT OF “ENVIRONMENTAL CONSCIOUSNESS” IN THE MODERN PSYCHOLOGICAL SPACE - Lysianska, Taisiia; Bielousova, Nataliia (PSYCHOLOGICAL JOURNAL, 2020)
The importance of the rational, efficient and secure use of our planet’s ecosystem resources is a major factor for development of an individual’s self-awareness as an agent of the outside world. It is a manifestation of an individual’s consciousness and self-consciousness in the ecosystem. Scientists emphasize the need to focus on the role of an individual’s activity in the ecological system. The study purpose is to perform literature review, illuminate the problems of psychology of consciousness and determine theoretical approaches to the “consciousness” concept that help develop the concept of “environmental consciousness”. Thus, the factors of future environmental professionals’ environmental consciousness formation could be identified. Therefore, approaches, forms, components forming the “environmental consciousness” were identified. In the modern psychological space, the concept of “consciousness” is studied by many psychologists, philosophers and sociologists and is understood as a higher form of reality reflection, common to society and associated with an individual’s worldview and thinking, as well as self-control and prediction of one’s own behaviour. For today, the following forms of consciousness have been formed: scientific, environmental, professional, philosophical, religious, pedagogical, moral, aesthetic, legal, political, etc. The following theoretical approaches, indicating the origin and development of the “consciousness” concept, were defined: cognitive, regulatory, hierarchical, structural, integrative. The “ecological consciousness” concept was singled out from the modern psychological space. The researchers who examine this concept usually use the cognitive and regulatory approaches. We analyzed various approaches to the study of “ecological consciousness” and reconstructed its evolution. The article authors focused on the motivational-value approach, which is effective for the formation of future environmental professionals’ environmental awareness. Ecological consciousness is a basic element of the worldview and the basis, with which an individual begin to understand their own relations with the nature in the evolutionary process. The formed ecological consciousness allows an individual to perceive the surrounding world and themselves in this world as an element of a single ecosystem. That is, during conscious activity, in the context of relations with the nature, an individual forms different substructures of ecological consciousness. The purpose of human interactions with the nature is to satisfy as much as possible the needs of society and the requirements for environmental conservation.